IMPACT OF THE LABIOPALATINAL FISSURE ON THE QUALITY OF LIFE OF CHILDREN AND ADOLESCENTS IN PERNAMBUCO - BRAZIL - Gomes Moreira, Andreia; Butini Oliveira , Luciana (Health and Society, 2021)
Cleft lip and palate are the most frequent anomalies of the face, which can compromise normal functions in addition to interfering with the patient’s quality of life. Oral health problems can impact daily life, being more striking for these patients due to their functional and aesthetic changes. The aim of the study was to evaluate the oral health-related quality of life of patients with cleft lip and/or palate at the Center for Attention to Face Defects (CADEFI/IMIP-PE). The sample consisted of 348 patients, 174 aged 8 to 12 years and 174 aged 13 to 18 years. The collection instrument used to measure quality of life was PedsQL 4.0. Data analysis was performed using the STATA 9.0 software, descriptive, observing the absolute and relative frequencies in relation to the demographic and clinical characteristics of the sample and measures of central tendency for the PedsQL 4.0 score and domains. Poisson regression with robust variance was performed to associate the total scores and individual domains of the PedsQL 4.0 with the types of cravings, their prevalence and demographic conditions. Subsequently, the selected variables were tested in the adjusted multivariate model, which could only be maintained if the variables presented p≤ 0.05. Robust rate ratios (RTR) and 95% confidence intervals (95% CI) were calculated. Practically all respondents (99.9%) reported some impact in at least one of the instrument’s domains. Children aged 13 to 18 years had a positive impact, better quality of life, compared to those aged 8 to 12 years. Multidisciplinary treatment protocols for the rehabilitation of patients with cleft lip and palate seek to restore function and aesthetics, helping to overcome stigma and integrating into social life, which can justify the favorable results of the assessment of the quality of life of these patients